2018
DOI: 10.18632/oncotarget.24649
|View full text |Cite
|
Sign up to set email alerts
|

Cold atmospheric plasma as a potential tool for multiple myeloma treatment

Abstract: Multiple myeloma (MM) is a fatal and incurable hematological malignancy thus new therapy need to be developed. Cold atmospheric plasma, a new technology that could generate various active species, could efficiently induce various tumor cells apoptosis. More details about the interaction of plasma and tumor cells need to be addressed before the application of gas plasma in clinical cancer treatment. In this study, we demonstrate that He+O2 plasma could efficiently induce myeloma cell apoptosis through the activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 62 publications
0
26
0
Order By: Relevance
“…Plasma-activated liquids display different biological actions which have been mainly attributed to the generation of RONS such as H 2 O 2 5,6 , NO 2 – 7 , ONOO − 8 , etc. These reactive species are known to be involved in a wide range of intracellular 6,7,9 and intercellular processes 10 and have shown a strong anti-cancer effect on several cancer cell lines in vitro 1117 and on subcutaneously xenografted tumors in vivo 14,1721 . Recently, proof of efficiency and selectivity in osteosarcoma was shown 10,2224 .…”
Section: Introductionmentioning
confidence: 99%
“…Plasma-activated liquids display different biological actions which have been mainly attributed to the generation of RONS such as H 2 O 2 5,6 , NO 2 – 7 , ONOO − 8 , etc. These reactive species are known to be involved in a wide range of intracellular 6,7,9 and intercellular processes 10 and have shown a strong anti-cancer effect on several cancer cell lines in vitro 1117 and on subcutaneously xenografted tumors in vivo 14,1721 . Recently, proof of efficiency and selectivity in osteosarcoma was shown 10,2224 .…”
Section: Introductionmentioning
confidence: 99%
“…These results might be due to the fact that SCC-15 cells respond to cisplatin treatment during the initial 6 h, and then apoptosis/necrosis is accelerated following cell death. Xu et al also reported that CAP increased caspase-9 activity of multiple myeloma and induced apoptosis/necrosis of cells [ 43 ]. Saadati et al also reported that indirect/direct treatment of B16F10 melanoma cells using CAP induces apoptosis-related protein expression, such as BAX/BCL-2 [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Toxicological studies were CAP at 75kV, IC 50 was 0.0087 µg/ml. CAP similarly generates ROS and can be localised by selective application process at a milli or micro scale to cancer cells [50,51]. Consistent with the findings regarding to oxidative stress correlation to cell death with AgNP and CAP continuously mounts the evidence to show that generation of ROS is highly related to the mechanism of AgNP and CAP with the results in current study showed that the cytotoxicity induced by AgNP alone, as well as the combinational treatment AgNP-CAP were efficiently prevented prior NAC treatment up to 10-fold (see Figure 3).…”
Section: Discussionmentioning
confidence: 99%